Emotif Istimewa Di Balik Lirik Lagu “Terpaut Oleh Waktu” Karya Danilla Riyadi - Annisa Ramadiyanti (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
The purpose of this study is to describe, analyze, and find the style of language contained in song lyrics adrift by the time of one of Danilla Jelita Poetri Riyadi's works in the Telisik Album. In the lyrics of the song Adrift by the time of the album Telisik there are interesting words for the author to study based on his language style. Time adrift means "a series of processes" (in one's romantic relationships). And the real meaning in the lyrics of this song is a person's hope for the idol, wanting to have and also wanting to be loved by him. Hoping if his feelings can be accepted by that loved one. This song also describes how a person who is immersed in his longing for his sweetheart but he realizes that he has it alone he has not. This research uses descriptive methods and qualitative approaches. Data analysis techniques begin by identifying words that contain language style. The research results of this article are exploring and clarifying the style of language as well as the meaning contained in the song